2017
DOI: 10.1504/ijtip.2017.091485
|View full text |Cite
|
Sign up to set email alerts
|

Are there any differences between family and non-family firms in the open innovation era? Lessons from the practice of European manufacturing companies

Abstract: Although there is an increased interest in studies on FFs and open innovation (OI) the existing knowledge is rather limited. This study explores the open innovation choices, their determinants and the relative innovation performance in FFs with respect to non-family firms. By means of an European survey involving Italian, Swedish, Finnish and UK family and non-family firms we aim at investigating whether FFs are adopting a peculiar behaviour in the open innovation era. In order to achieve this goal, we rely on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…In order to surpass some of these limitations, other studies have included more details, by referring, for instance, to in-depth case studies on a specific type of OI and CN partner, such as crowdsourcing (e.g., [39,40]), or even those regarding the innovation related to the crossindustry [41]. Other studies have suggested specific partner types, regarding determined innovation problems (e.g., [42][43][44][45][46]). This study also accounts for these approaches with the aim of increasing generalizability.…”
Section: Partner Selection By Using Multicriteria Decision-making (Mcdm) Approachesmentioning
confidence: 99%
“…In order to surpass some of these limitations, other studies have included more details, by referring, for instance, to in-depth case studies on a specific type of OI and CN partner, such as crowdsourcing (e.g., [39,40]), or even those regarding the innovation related to the crossindustry [41]. Other studies have suggested specific partner types, regarding determined innovation problems (e.g., [42][43][44][45][46]). This study also accounts for these approaches with the aim of increasing generalizability.…”
Section: Partner Selection By Using Multicriteria Decision-making (Mcdm) Approachesmentioning
confidence: 99%
“…In line with this reasoning, De , through a cross-case study between family and non-family firms, show that family firms are more inclined to rely on a higher number of external collaboration when scientific partners and/or suppliers/customers rather than competitors are involved. Lazzarotti et al (2017) provide an additional and new perspective concerning OI strategies in family firms. Indeed, despite the lower search breadth explored among the family firm sub-sample, when it comes to the depth, higher levels of intensity in the family firms' collaboration process with external partners emerged.…”
Section: Open Innovation In Family Firmsmentioning
confidence: 99%
“…As might be assumed, active participation of family members in the ownership, management and board shape family firms' discretion over decision-making process and so the strategy of the firm. Thus, differences among the level of family member involvement, the inclusion of non-family members in the ownership, management and board (Classen et al, 2012;Lazzarotti et al, 2017), may increase or decrease the family firms' ability to engage in OI activities. Also, the family generation in control, intergenerational involvement or even specific characteristics of family managers, such as level of education, external professional experiences, Chief Executive Officer (CEO) duality (Classen et al, 2012;Alberti et al, 2014;Serrano-Bedia et al, 2016), may lead to interesting findings.…”
Section: Family-specific Characteristics/factors Affecting Open Innovation Behaviormentioning
confidence: 99%
See 2 more Smart Citations